Erin Brockovich - Steven Soderbergh; Albert, Finney; Conchata Ferrell; David Brisbin; Dawn Didawick; George Rocky Sullivan; Valente Rodriguez; Julia Roberts (USA Jersey Films, 2000)
Erin Brockovich is an unemployed single mother, desperate to find a job, but is having no luck. This losing streak even extends to a failed lawsuit against a doctor in a car accident she was in. With no alternative, she successfully browbeats her lawyer to give her a job in compensation for the loss. While no one takes her seriously, with her trashy clothes and earthy manners, that soon changes when she begins to investigate a suspicious real estate case involving the Pacific Gas & Electric Company. What she discovers is that the company is trying quietly to buy land that was contaminated by hexavalent chromium, a deadly toxic waste that the company is improperly and illegally dumping and, in turn, poisoning the residents in the area. As she digs deeper, Erin finds herself leading point in a series of events that would involve her lawfirm in one of the biggest class action lawsuits in American history against a multi-billion dollar corporation.
An unemployed single mother becomes a legal assistant and almost single-handedly brings down a California power company accused of polluting a city's water supply.
Susannah Grant
Language: English
Subtitles: English, Deutsch, Nederland, Arabic, Bulgarian, Czech, Dansk, Suomi, Hindi, Magyar, Islenka, Turkish, Norsk, Polish, Svenska
Keywords: Drama; Biography